The Consumer Standards in Russia: Key Features and the Limits - Pishnyak, Alina; Khalina, Natalya; Nazarbaeva, Elena (Journal of Economic Sociology, 2025)
The article discusses consumer standards existing today in Russia. Based on materials from focus group discussions conducted in 2023, various types of standards are identified and a detailed description of the capabilities of each is provided in the context of individual consumption spheres (from purchasing food products to paying for medical and educational services). Four standards: “Comfort,” “Norm,” “Hard, but livable,” and “Very bad”  illustrate the differentiation of society and provide insight not only into consumption benchmarks but also into markers of deteriorating financial status for different population groups. Notions of consumer standards are constructed in the population’s consciousness based on income possibilities, and the final model is a hierarchical composition in which the transition from one standard to another occurs with changes in income. The progression from the ‘Comfort’ standard to the ‘Very bad’ standard involves increased choice constraints: the lower the level, the more people are forced to seek low prices and save, resulting in reduced access to a variety of products. Nevertheless, one can note the retention of standards of ‘pre-pandemic normalcy’ in the population’s consciousness and a gradual acceptance of the reality of recent years. This indicates the rigidity of notions about consumer standards: they evolve over time (including due to the introduction of new products and services, technological advancements, etc.), but this evolution is not instantaneous.